Customer Intention to Quantify the Feasibility of BUMD during The Modern Economic Era: Case Study of BUMD in Kampar Regency - Samsurijal Hasan; Septa Diana Nabella; Utami Yerikania (Yayasan Riset dan Pengembangan Intelektual, 2022)
In the modern economic era, success business sector should give attention to how global policies, as well as regional policies, certainly affects the intensity and direction of business policies. Customer intention was to play the priority of the company to create and gain the market. Where the customer intention will be reflecting the customer's behaviour and view against the product or the business unit. This study was to determine the customer intention to quantify the feasibility of BUMD during the modern Economic Era. This study was limited to regency-owned BUMD and the BUMD was established more than 15 years. This study was conducted on customers from Bank BPR Sarimadu. The Slovin formula technique was chosen in this study where the number of samples in this study is as many as 100 people from 300 customers, with an error rate of 10%. the result was defined that the Customer Intention of BUMD is explained by Professionalism (X1), Marketing Quality (X2), and Service Quality (X3) variables by 69.5%, while 34.5% is explained by other variables not examined in this study. This study also mentions that its major contribution to customer intention was influenced by these factors. Based on this study, professionalism, marketing quality along with service quality is the main parameters for increasing the interest of the customer to become BUMD loyal members. Thus, professionalism becoming a top priority for enhancing the BUMD image or company image. By improving the quality of management, marketing quality, and service quality of the company, BUMD customers will feel more confident when using chosen of BUMDs products and services. Keywords: BUMD; Customer Intention; Service Quality, Professionalism, Marketing Quality.